Attitudes of physiotherapists in Botswana to treating people living with HIV/AIDS - M. Kambole; P. Struthers (South African Journal of Physiotherapy, 2009)
Physiotherapists are increasingly treating people living with HIV /AIDS.However, there is little information reported on either their attitudes when providingtreatment to people with HIV /AIDS, or what facilitates positive attitudes. This studyaimed to determine the attitudes of physiotherapists in Botswana towards treating people living with HIV /AIDS. A  qualitative approach was used with a purposive sample of 10 physiotherapists working in hospitals and private clinics in Gaborone and Ramotswa. In-depth interviews were conducted with individual physiotherapists, utilising an interview guide in. The results indicated that most physiotherapists had a positive attitude towards treating people living with HIV /AIDS. The positive attitude was associated with interrelated factors including their experiencewith people living with HIV /A IDS (PLW HA ); knowledge of HIV /AIDS; job satisfaction; and a belief in a duty to treatall. A  few physiotherapists had a negative attitude which was related to being judgmental and to a fear of acquiring HIVthrough occupational infection.